MANAJEMEN KEPALA SEKOLAH DALAM MENINGKATKAN KOMPETENSI PROFESIONAL GURU DI SEKOLAH MENENGAH PERTAMA LAZUARDI HAURA BANDAR LAMPUNG TAHUN PELAJARAN 2023/2024 - Fitriarni (UNISAN JURNAL, 2024)
Success in the world of education can be measured from various aspects. Starting from the quality of students, educators, the atmosphere of the school environment to the school administration system. However, the main factor that most influences the dynamics of education in schools is the leader who is responsible for the running of the educational milliu, in this case the school principal. To carry out his duties as a manager in improving teacher professionalism, a school principal must have the ability and understanding of principal management well. Apart from that, teachers are also expected to not only transfer knowledge but be able to provide maximum performance accompanied by high motivation. This research aims to describe and examine in more depth how the principal's leadership and the principal's management steps improve teacher professionalism. This type of research is in the form of qualitative research with a case study design by taking data sources from school principals and teachers through observation, interviews and documentation data collection techniques. Data were analyzed in the form of data reduction, data presentation and drawing conclusions. The research results show that the principal's management at SMP Lazuardi Haura Bandar Lampung consists of planning, implementing, supervising and organizing. The principal as a manager plays the role of educator, manager, supervisor, motivator and innovator. The management steps taken by the school principal are carrying out supervision, providing rewards, motivating and encouraging continuing education. Supporting factors for school principal management in increasing teacher professionalism can be caused by fulfilling teaching staff, discipline, motivation and a conducive environment. The inhibiting factors are the small number of certified honorary teachers, time management of teachers and staff and a lack of understanding of information technology. This research has implications for the need for leaders to pay attention to their subordinates through developing teacher professionalism.